A novel species of Heterophoxus Shoemaker, 1925 (Crustacea, Amphipoda, Phoxocephalidae) from southeast and southern Brazil, with an identification key to world species of the genus - Andrade, Luiz F.; Senna, André R. (European Journal of Taxonomy, 2020)
This paper describes a novel species of the genus Heterophoxus Shoemaker, 1925 from Brazil. The material examined was collected during the Mini Biological Trawl Project, off southeast and southern Brazil’s coast off the states of Rio de Janeiro, Santa Catarina, and Rio Grande do Sul, ranging in depth from 25 to 128 meters. The new species, H. shoemakeri sp. nov., is similar to H. videns K.H. Barnard, 1930; however, the former species can be distinguished by: pereopod 7 basis posterior margin serrate with acute teeth, merus posterior margin not produced; epimeral plate 3 posteroventral corner with a longer acute projection, posterior margin almost straight; uropod 3 outer ramus article 2 clearly notable in both sexes. For Brazilian waters, this is the second record of the genus and the first species described with type material from the country. Besides that, we provide an identification key for the world species of Heterophoxus and a distribution map for the new species.